Modifiable Risk Factors for Stroke in Syria: A Nationwide Multi-centre Case-Control Study - Mhd Mustafa Albitar; Subhia Maya; Khaled Kalalib Al Ashabia; Ghassan Hamzeh; Ameer Kakaje (Scientific Reports)
Abstract Stroke is the second-leading cause of death worldwide, including in Syria, and the third-leading cause of death and disability combined. With approximately 90% of strokes worldwide linked to modifiable risk factors, identifying and quantifying these factors within a specific population is essential for effective prevention. This is the first study to investigate primary risk factors for stroke in Syria. This study included the six primary stroke centres across four major cities in Syria. Data was collected through case files and a questionnaire answered by the cases or their proxies through personal interviews, as well as selected controls. A total of 411 cases were recruited, comprising 363 ischemic strokes (IS) and 48 haemorrhagic strokes, and with a matched ratio of 1:1 for age and sex. IS was significantly associated with multiple chronic conditions including atrial fibrillation AF [AOR 5.04 (2.64–9.62)], high body mass index (overweight [AOR 2.09 (1.28–3.40)], obesity [AOR 4.17 (2.32–7.50)]), hypercholesterolemia [AOR 2.10 (1.34–3.28], hypertension HTN [AOR 1.83 (1.23–2.73)], and diabetes mellitus DM [AOR 1.79 (1.18–2.71)]. Moreover, several lifestyle risk factors contributed to IS: Alcohol consumption [AOR 4.80 (1.72–13.41)], a diet lacking fruits and vegetables [AOR 2.04 (1.28–3.23)], and low physical activity PA [AOR 1.75 (1.01–2.86)]. Notably, over 40% of the population exhibited medication nonadherence. IS showed no significant association with cigarette smoking, heart failure (HF), ischemic heart disease (IHD), or a family history of stroke (p > 0.05). In contrast, haemorrhagic stroke was linked to higher BMI, HTN, DM, and AF (p < 0.05), but not to hypercholesterolemia, cigarette smoking, IHD, or HF (p > 0.05). This first nationwide multicentre case-controlled study in Syria identified critical modifiable risk factors for stroke, including hypertension, diabetes, atrial fibrillation, and obesity, with high rates of medication non-adherence, especially among hypertensive patients, complicating stroke risk. These findings underscore the urgent need for targeted health interventions promoting lifestyle modifications, medication adherence, and public health policies tailored to Syria’s current resource-limited context to reduce the stroke burden and improve population health.